The Effect of Corporate Environmental Responsibility (CER) on Firm Value with Good Corporate Governance (GCG) as a Moderating Variable - Zakia Juliani; Lismawati Lismawati; Sriwidharmanely Sriwidharmanely; Putri Indah Lestari (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This studyaims to examine the effect of Corporate Environmental Responsibility on Corporate Value with Good Corporate Governance (GCG) as a moderation variable. This research is an empirical research based on financial statement data on manufacturing companies listed on the IDX for the 2020-2021 period. The sample selection technique uses purposive sampling with a total of 40 samples. Data analysis techniques use regression tests and Moderated Regression Analysis (MRA). Environmental Performance is measured using PROPER rating, Good Corporate Governance (GCG) component is measured using Managerial Ownership, Institutional Ownership, Audit Committee, Board of Commissioners, and Independent Board of Commissioners. The results of the research findings, namely: (1) Corporate Environmental Responsibility (CER) has a significant effect on Company Value. (2) Managerial Ownership, Institutional Ownership and Audit Committee cannot moderate the relationship of Corporate Environmental Responsibility (CER) to Corporate Value. (3) The Board of Commissioners and the Board of Independent Commissioners may moderate the relationship of Corporate Environmental Responsibility (CER) to Corporate Value.